Ovarian Hyperstimulation Syndrome, the Master of Disguise?. (22nd February 2015) - Ironside, Emily Charlotte; Hotchen, Andrew James
Abstract : The use of IVF has risen dramatically over the past 10 years and with this the complications of such treatments have also risen. One such complication is ovarian hyperstimulation syndrome with which patients can present acutely to hospital with shortness of breath. On admission, a series of blood tests are routinely performed, including the d-dimer. We present a case of a 41-year-old lady who had recently undergone IVF and presented with chest pain and dyspnoea. In the emergency department, a d-dimer returned as mildly elevated. Consequential admission onto MAU initiated several avoidable investigations for venous thromboembolism. Careful examination elicited a mild ascites and a thorough drug history gave recent low molecular weight heparin usage. Ultrasound scan of the abdomen subsequently confirmed the diagnosis of severe OHSS. The d-dimer should therefore be used to negate and not to substantiate a diagnosis of VTE. This case report aims to highlight the importance of OHSS as an uncommon cause of dyspnoea but whose prevalence is likely to increase in the forthcoming years. We discuss the complications of the misdiagnosis of OHSS, the physiology behind raised d-dimers, and the potential harm from incorrect treatment or inappropriate imaging.